1999
DOI: 10.1093/hmg/8.10.1893
|View full text |Cite
|
Sign up to set email alerts
|

Nonsense-mediated mRNA decayin health and disease

Abstract: All eukaryotes possess the ability to detect and degrade transcripts harboring premature signals for the termination of translation. Despite the ubiquitous nature of nonsense-mediated mRNA decay (NMD) and its demonstrated role in the modulation of phenotypes resulting from selected nonsense alleles, very little is known regarding its basic mechanism or the selective pressure for complete evolutionary conservation of this function. This review will present the current models of NMD that have been generated duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

20
671
1
3

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 927 publications
(695 citation statements)
references
References 81 publications
20
671
1
3
Order By: Relevance
“…First, PTCs are common: nonsense and frameshift mutations are present in approximately one-third of mutations that cause human genetic disease 28,29 . Second, nonsense codons in all internal exons are capable of triggering NMD 23 , which means that mRNA levels will be reduced by most nonsense and frameshift mutations [28][29][30] ; therefore, PTCs generally result in milder phenotypes as compared with missense mutations, as has been postulated in several human diseases including osteogenesis imperfecta 31 , Stickler syndrome 32 and Marfan syndrome 33,34 . Third, on the basis that NMD has a potential role in most disease-causing PTCs, it has been proposed that haploinsufficiency is the most predictable pathogenetic mechanism underlying heterozygous nonsense alleles 29 .…”
Section: Discussionmentioning
confidence: 99%
“…First, PTCs are common: nonsense and frameshift mutations are present in approximately one-third of mutations that cause human genetic disease 28,29 . Second, nonsense codons in all internal exons are capable of triggering NMD 23 , which means that mRNA levels will be reduced by most nonsense and frameshift mutations [28][29][30] ; therefore, PTCs generally result in milder phenotypes as compared with missense mutations, as has been postulated in several human diseases including osteogenesis imperfecta 31 , Stickler syndrome 32 and Marfan syndrome 33,34 . Third, on the basis that NMD has a potential role in most disease-causing PTCs, it has been proposed that haploinsufficiency is the most predictable pathogenetic mechanism underlying heterozygous nonsense alleles 29 .…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that no additional RNA band was detected using either probe, which showed the absence of additional hybrid RNA molecules that could produce hybrid proteins containing any portion of torsinA. Nonsense-mediated mRNA decay has been well documented in mammalian cells (Frischmeyer, 1999). Western blot analysis showed that homozygous Dyt1 STOP mice expressed approximately 36% less protein than the level expressed in WT mice ( Fig.…”
mentioning
confidence: 90%
“…Normal MLH1 expression, however, has also been described in tumours from subjects with small and large in-frame deletions and truncating mutations [51,55]. As the c.2252_2253delAA mutation is located in the last exon of MLH1, it is unlikely that the mutant mRNA is degraded by nonsense-mediated decay (NMD) [56]. Accordingly, Sanger sequencing of cDNA by 3 different carriers showed the balanced presence of both the wild-type and mutated transcripts (as shown in Online Resource 1).…”
Section: Discussionmentioning
confidence: 99%